Audiência pública no Supremo Tribunal Federal - Moreira, Diogo Rais Rodrigues (2011)
This dissertation is based on the procedural branch of Constitutional Law, whose central goal laid on the public hearings held before the Brazilian Supreme Court so far. Facing this procedural institution, still incipient in the Brazilian judicial system, we are interested in identifying its origins and workability, beginning with a study of its legal creation and the spread of its use in the administrative bureaucracies and in the legislative activity. The public hearing went through a long road before knocking on the Judiciary s doors, and its exhaustive and uneasy task did not end by then. It was necessary to open up these doors, but, in order to effectively have its place, strong oppositions born from an array of taboos had to be faced and ceased slowly. At the Brazilian judiciary its triumph started in the Supreme Court, walking through the Supremo Tribunal Federal bars. Between its legal creation and the first public hearing held passed eight years, and more than 500 thousand lawsuits. In the history of this court, we counted five public hearings which were held, each of them in its own way, being their methodological and decisional variations the inspiration of this work; therefore, this dissertation s core is the empirical research of this new legal institute whose legal regime and concepts are still under construction